Orofacial Clefting – An Extensive Review - Ashiq, T. (International Journal of Pharmaceutical & Biological Archive, 2021)
Groove in the palatal vault makes an abnormal communication between oral and nasal cavity is known as orofacial cleft. It is an uncommon presentation in day-to-day clinical practice. According to the World Health Organization, children with the complaint of oro-facial clefts found to be high in India. Children are commonly suffering from functional and esthetical problems due to orofacial clefting. Globally, an estimated 200,000 babies are born with a cleft lip (CL), palate or both each year in the United States. Etiology may be congenital or acquired. Palatal and Alveolar cleft defects are the most common etiological factors. CL and cleft palate (CP) can sometimes develop in combination with a syndrome due to genetic causes. The acquired causes may be infections, trauma, postsurgical complications, neoplasms, periapical pathology, radio, and chemo necrosis. Clinical features such as defective speech, and upper respiratory tract and ear infections, fetid odor, bad taste, and nasal regurgitation of food are the associated consequences of oro-nasal communication. Therefore, this malformation syndrome is an important public health problem. Many CP and CL develop due to the combination of genetic and environmental factors. There are more than 400 genes linked to formation of CL and palate. Some environmental factors associated with cleft include medications, deficiency of folic acid, cigarette, drugs or alcohol conception during pregnancy. In this article, we review the anatomy, embryology, epidemiology clinical manifestations, and treatment options of the orofacial cleft